Herpes Zoster Duplex Symmetricus in an immunocompetent 70-year female - Mankesh Lal Gambhir; Yukti Aggarwal; Kritika Pandey; Suresh Kumar Malhotra (Our Dermatology Online, 2014)
Herpes zoster is a neuroectodermal viral infection which afflicts one or more closely grouped, spinal or cranial nerves, resulting in unilateral radicular pain and vesicular eruption limited to a dermatome innervated by that nerve [1]. Bilateral involvement is rare, bilaterally symmetrical involvement is extremely rare. We hereby report a case of bilaterally symmetrical herpes zoster in an old immunocompetent female.